Peninjauan Hukum Menurut Hukum Adat Kampar: Sumbangan dalam Mewujudkan Hukum yang Responsif - Haniah Ilhami (The Constitutional Court of the Republic of Indonesia, 2022)
The development of Indonesian constitutional law, especially judicial review, is influenced by the liberal continental and Anglo-Saxon legal systems. Meanwhile, Kampar customary law already has a legal review system with the philosophy